Finding your leadership style : a guide for educators - Glanz, Jeffrey (Association for Supervision and Curriculum Development, 2002)
What makes a good educational leader? How can you be one? Is a job candidate an effective leader who can work with students and staff in your school or district? According to author Jeffrey Glanz, each of us has natural leadership abilities. Although no single leadership style is better than another, matching a person's style with an assignment leads to success for the person, his colleagues, and the organization. The key is to identify and actualize each person's natural leadership style. Full descriptions of the seven types of leaders-Dynamic Aggressives, Dynamic Assertives, Dynamic Supportives, Adaptive Aggressives, Adaptive Assertives, Adaptive Supportives, and Creative Assertives-afford valuable insight into your own behaviors and strengths of those around you. Glanz uses vivid, authentic scenarios to illustrate the qualities of each leadership type, and identifies seven virtues that are critical for all leaders and yet are often overlooked in educational leadership programs. An invaluable aid to teachers, supervisors, district leaders, this book provides questionnaires and focus questions to help you analyze leadership potential in yourself and in colleagues. The author also shows you how to go about the crucial process of matching leadership qualities with specific jobs in the educational system, from teacher to superintendent. Understanding the natural leadership qualities and virtues helps you to create an educational environment that is characterized by excellence.